1998
DOI: 10.1038/bjc.1998.207
|View full text |Cite
|
Sign up to set email alerts
|

The antiproliferative activity of all-trans-retinoic acid catabolites and isomers is differentially modulated by liarozole-fumarate in MCF-7 human breast cancer cells

Abstract: SummaryThe clinical use of all-trans-retinoic acid (ATRA) in the treatment of cancer is significantly hampered by the prompt emergence of resistance, believed to be caused by increased ATRA catabolism. Inhibitors of ATRA catabolism may therefore prove valuable for cancer therapy. Liarozole-fumarate is an anti-tumour drug that inhibits the cytochrome P450-dependent catabolism of ATRA. ATRA, but also its naturally occurring catabolites, 4-oxo-ATRA and 5,6-epoxy-ATRA, as well as its stereoisomers, 9-cis-RA and 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…This is in line with earlier studies suggesting that VAD is associated with carcinogenesis (Wolbach and Howe, 1925), and upregulation of CYP26A1 has recently been shown in a number of cancer cell types (Sonneveld et al, 1998;Van heusden et al, 1998;Shelton et al, 2006;Chang et al, 2008). If increased RA metabolism is solely responsible for the apoptogen desensitizing effect, our results would imply that in a state of RA deficiency, cells may be less susceptible to apoptosis following the acquisition of DNA damage.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in line with earlier studies suggesting that VAD is associated with carcinogenesis (Wolbach and Howe, 1925), and upregulation of CYP26A1 has recently been shown in a number of cancer cell types (Sonneveld et al, 1998;Van heusden et al, 1998;Shelton et al, 2006;Chang et al, 2008). If increased RA metabolism is solely responsible for the apoptogen desensitizing effect, our results would imply that in a state of RA deficiency, cells may be less susceptible to apoptosis following the acquisition of DNA damage.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the fact that the CYP26 enzymes may have a similar but separate role in limiting the consequences of fluctuations in nutritional vitamin A, the possibility that pathological conditions such as cancer might involve aberrant expression of CYP26A1 has recently emerged from several studies. Accumulating evidence has shown that enhanced RA catabolic activity has been observed in various types of cancer and elevated CYP26A1 expression has been detected in a number of cancer cell types (Sonneveld et al, 1998;Van heusden et al, 1998;Shelton et al, 2006;Chang et al, 2008). On the other hand, our previous study has shown that the cells expressing CYP26A1 gain significant resistance to apoptosis because of the state of reduced bioavailability caused by the metabolic inactivation of RA (Osanai and Petkovich, 2005).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…After centrifugation for 10 min at 780 g, the supernatant was analyzed for the presence of RA metabolites. Reverse-phase HPLC analysis was carried out as described previously (Van heusden et al, 1998).…”
Section: Hplc Analysismentioning
confidence: 99%
“…In vitro, liarozole-fumarate has been shown to enhance both the antiproliferative and differentiation-inducing activity of RA (Wouters et al, 1992;Van heusden et al, 1996Van heusden et al, , 1998. In vivo, liarozole-fumarate increases endogenous RA levels both in plasma and tissues (Smets et al, 1995).…”
mentioning
confidence: 99%